Personal digital archiving: influencing factors and challenges to practices. Issue 2 (19th June 2017) - Sinn, Donghee; Kim, Sujin; Syn, Sue Yeon
Abstract : Purpose: The purpose of this paper is to investigate the associations of personal archiving behaviors to factors and challenges that have been assumed to affect personal digital archiving strategies. Design/methodology/approach: This study created an online survey to understand general patterns of personal digital archiving practices and related phenomena. The survey was employed to investigate to what extent people show a certain behavior or feel certain factors and challenge when archiving personal digital content. Findings: Some of the findings of this study regarding specific personal digital archiving practices were in accordance with existing studies. However, the associations between digital archiving challenges and archiving practices were not observed statistically significantly as assumed in previous studies. General technology efficacy and the awareness of the importance of personal records appeared to influence personal archiving practices. Research limitations/implications: This study used Amazon's Mechanical Turk. As this is not a commonly used internet service, the workers here could have higher than average levels of internet efficacy. This possibility may have affected the demographics, and the survey responses may be biased in this respect. Practical implications: As the study results suggest that technology efficacy and personal heritage awareness are the influencing factors of personal digital archiving, these are the areas where information professionals can involve in assisting users for future cultural heritage. Originality/value: This is the first study that develops measures for personal digital archiving related practices and perceptions that the previous qualitative studies have identified. With these measures, it examines the general status of individuals' archiving strategies and the overall associations of digital archiving challenges as well as looking into other technological and personal factors.